AZ-ZAHRAWI MEMORIAL LECTURE: Psychospirituality in Medicine - Shaharom, Mohamed Hatta (International Journal of Human and Health Sciences (IJHHS), 2022)
“O Allah, Most Benevolent, Most Merciful. We seek Your Guidance and Blessings in our efforts to gain knowledge; and to be instruments of Your Mercy as we serve humankind regardless of race or creed.” The psychospiritual domain of the four-domain holistic approach to health has been a reality without a name during the ascent of Western modern or conventional medicine of the 19th and the greater part of the 20th centuries Common Era (CE). The focus then was on the biomedical model of medicine. Alongside this, the 1900 Interpretation of Dreams of Sigmund Freud (pronounced: froid) ushered in a new era of psychoanalysis and sexual liberalism that influenced the whole of Western life, including medicine. Freud considered religion as a neurosis, a manifestation of ill health. Just as Freud was about to be dethroned from the altar of Western secular psychology, George Engel conceptualised the biopsychosocial model in health and medicine in 1977 CE. By the late 1980s, research on the role and effects of spirituality on health and illness appeared on the horizon of scientific research. Spirituality may include or exclude the role of religions in a person's life. Since time immemorial, spirituality has always existed in the paradigm of those who espoused religiosity in their lives. Now as we approach the year 2022 CE, the psychospiritual role in health and illness is considered part and parcel of holistic health. Any discussion and training in medicine that is without the inclusion of the psychospiritual sciences must be considered incomplete. It is trendy and a necessity now to discuss mental health during this SARS-CoV-2 onslaught, along with the disease that it brings. Every medical student understands and appreciates the universality of psychological or mental health. However not all medical practitioners appreciate the necessity of the spiritual domain to complete the four-domain holistic paradigm in life and medicine. Fortunately, a growing number of therapists and clinicians are able to see the potential of spirituality in the management of patients of various beliefs including the whole range of believers and non-believers; among them are atheists, agnostics, narcissists, the religious and the secular. The uninitiated and the cynic may argue that spirituality is not a panacea, i.e. a cure for all ills. However, for the discerning therapist and the insightful clinician, spirituality is functional in treatment or ‘ilāj (, ) علاج as the client and patient inch along in the process of healing or shifā’(. ) شفاء Even in the prevention or al-wiqāyah ( الوقاي ة ) of illnesses, the spiritual domain must never be ignored. Since the spiritual domain is a reality in life, it has a significant part to play in preserving health and the treatment of illness. “Enlightened medicine is a practice humbled in the presence of the Divine, and evidenced by the signs of the Divine.” International Journal of Human and Health Sciences Supplementary Issue: 2022 Page: S4